Sunlight Exposure and Protection Behavior as Prevention of Skin Cancer in Nursing Students - Raden Nabilah Putri Fauziyyah; Maria Komariah; Yusshy Kurnia Herliani (Indonesian Journal of Cancer, 2023)
Background: Skin cancer ranks fifth in the world. Melanoma, a type of skin cancer, ranks 23rd in Indonesia. Meanwhile, deaths caused by skin cancer are more than half of the number of new cases in Indonesia. Indonesia is a country that lies across the equator. It makes Indonesia have longer exposure to sunlight and a higher UV index. This study aims to describe the sunlight exposure level and protection behavior among nursing students.Methods: The samples of this study were 248 respondents from the Faculty of Nursing, Universitas Padjadjaran, who were recruited with a convenience sampling technique. Data were collected using a modified Sun Exposure Behaviour Inventory (SEBI). The data were processed using SPSS statistical software to determine behavioral descriptions and exposure to sunlight. Then, the result of the data analysis was performed with descriptive analysis (frequency and percentage).Results: The result of this study showed that most of the respondents (84.3%) always used longsleeved clothes to cover their shoulders. Most respondents (85.9%) used sunscreen with a Sun Protection Factor (SPF) of 15 or more, and more than half of the respondents (68.5%) used sunscreen that can protect from Ultraviolet A (UVA) and Ultraviolet B (UVB). Most respondents (76.2%) never spent time under natural or artificial Ultraviolet Radiation (UVR) to get the desired brown skin. More than half of the respondents (66.9%) had never sunbathed in the last 12 months. Conclusions: More than half of the respondents had adequate protective behavior against sun exposure and had moderate sun exposure. Using sunscreens with a higher SPF has shown a stronger preventive effect. Therefore, regular use of sunscreen can decrease the risk of skin cancer.